The Concept of Multidisciplinary Education by Mohammad Natsir and Its Implementation at STID Moh. Natsir - Askar Patahuddin; Didin Hafidhuddin; Hasbi Indra; Budi Handrianto; Syamsuar Hamka (Universitas Muhammadiyah Enrekang, 2023)
Quality education is one that produces graduates who possess not only proficiency in a single field of study but beyond that (multidisciplinary). The various issues concerning the religious community, nation, and social dynamics of Indonesian society demand that graduates from higher education institutions have skills in more than one area of study. This research aims to uncover the concept of multidisciplinary education by Moh. Natsir and its implementation at College for Islamic Preaching (STID) Moh. Natsir. The research method used is descriptive qualitative, focusing on the literature related to the subject and employing content analysis to construct Moh. Natsir's educational concept. The findings reveal that Moh. Natsir advocates for quality and inclusive education by integrating studies of history and politics, promoting freedom and independent thinking, advocating for an understanding of Islamic democracy, combining literature and language, strengthening unity and Indonesian nationalism, and also integrating just economics and development to improve the welfare of the people. From this concept, Moh. Natsir represents a graduate of multidisciplinary education who applies this approach to all aspects of their activities, enabling them to address the challenges faced by the community and the nation in a holistic manner.